2019
DOI: 10.2196/11854
|View full text |Cite
|
Sign up to set email alerts
|

An Internet-Based Self-Testing Model (Easy Test): Cross-Sectional Survey Targeting Men Who Have Sex With Men Who Never Tested for HIV in 14 Provinces of China

Abstract: Background With China’s explosive internet growth, activities such as socializing and partner seeking among men who have sex with men (MSM) has also become Web based through popular services such as Blued. This creates a new mode of health promotion with the potential to instantly reach large numbers of MSM, including those who rarely access traditional offline testing facilities. Objective This study aimed to assess the feasibility of the Easy Test in increasing access… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 21 publications
(19 reference statements)
6
46
0
Order By: Relevance
“…[30] Similar studies con rm that HIVST is acceptable. [4,31,32] We strengthen the growing literature of the acceptability of HIVST among MSM, by also con rming the costeffectiveness of HIVST, compared to facility-based testing. We found that the cost per person tested using HIVST was $14.57, which is comparable to a systematic review of HIVST in sub-Saharan Africa that reported an average of $12.39 per person tested (Nurilign Ahmed, London School of Hygiene and Tropical Medicine, personal communication), and cheaper than the estimate from the US: $61 per person tested.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…[30] Similar studies con rm that HIVST is acceptable. [4,31,32] We strengthen the growing literature of the acceptability of HIVST among MSM, by also con rming the costeffectiveness of HIVST, compared to facility-based testing. We found that the cost per person tested using HIVST was $14.57, which is comparable to a systematic review of HIVST in sub-Saharan Africa that reported an average of $12.39 per person tested (Nurilign Ahmed, London School of Hygiene and Tropical Medicine, personal communication), and cheaper than the estimate from the US: $61 per person tested.…”
Section: Discussionsupporting
confidence: 58%
“…[1][2][3] In 2017, MSM accounted for 26% of all newly reported HIV cases in China, compared with 15% in 2011. [4] The global strategy to control the HIV epidemic hinges on early diagnosis and treatment of HIV. [5] A low HIV testing rate is one of the important reasons for the ongoing spread of HIV among MSM in China.…”
Section: Introductionmentioning
confidence: 99%
“…[15]In China, the demand for and acceptability of HIVST among MSM has been high, and many Chinese local community-based-organizations (CBOs) are working with health bureaus in piloting HIVST among MSM. [16,17] No policies or guidelines are in place to improve integrative syphilis testing for MSM in China; only one cross-sectional survey study with Chinese MSMfound that 92.5% of syphilis self-testers did HIVST at the same time,demonstrating the feasibility of integrating syphilis self-testing into HIV self-testing services. [18]Nevertheless, this study did not explore strategies for further expanding testing uptake.…”
Section: Introductionmentioning
confidence: 99%
“…We have successfully conducted a large study of MSM who were using HIVST for the first time, which demonstrated widespread acceptance. 33 …”
Section: Methodsmentioning
confidence: 99%
“…We have successfully conducted a large study of MSM who were using HIVST for the first time, which demonstrated widespread acceptance. 33 After randomisation, doctors will provide the participants in the intervention group face-to-face and paper-based HIVST instructions. All information and demonstration videos will be available on study sites' WeChat and Tencent QQ account.…”
Section: Self-testing Kits and Testing Proceduresmentioning
confidence: 99%